Improving adherence to Standard Precautions for the control of health care-associated infections - Moralejo, Donna; El Dib, Regina [UNESP]; Prata, Rafaela A. [UNESP]; Barretti, Pasqual [UNESP]; Corrêa, Ione [UNESP] (Wiley, 2018)
Background: 'Standard Precautions' refers to a system of actions, such as using personal protective equipment or adhering to safe handling of needles, that healthcare workers take to reduce the spread of germs in healthcare settings such as hospitals and nursing homes. Objectives: To assess the effectiveness of interventions that target healthcare workers to improve adherence to Standard Precautions in patient care. Search methods: We searched CENTRAL, MEDLINE, Embase, CINAHL, LILACS, two other databases, and two trials registers. We applied no language restrictions. The date of the most recent search was 14 February 2017. Selection criteria: We included randomised trials of individuals, cluster-randomised trials, non-randomised trials, controlled before-after studies, and interrupted time-series studies that evaluated any intervention to improve adherence to Standard Precautions by any healthcare worker with responsibility for patient care in any hospital, long-term care or community setting, or artificial setting, such as a classroom or a learning laboratory. Data collection and analysis: Two review authors independently screened search results, extracted data from eligible trials, and assessed risk of bias for each included study, using standard methodological procedures expected by Cochrane. Because of substantial heterogeneity among interventions and outcome measures, meta-analysis was not warranted. We used the GRADE approach to assess certainty of evidence and have presented results narratively in 'Summary of findings' tables. Main results: We included eight studies with a total of 673 participants; three studies were conducted in Asia, two in Europe, two in North America, and one in Australia. Five studies were randomised trials, two were cluster-randomised trials, and one was a non-randomised trial. Three studies compared different educational approaches versus no education, one study compared education with visualisation of respiratory particle dispersion versus education alone, two studies compared education with additional infection control support versus no intervention, one study compared peer evaluation versus no intervention, and one study evaluated use of a checklist and coloured cues. We considered all studies to be at high risk of bias with different risks. All eight studies used different measures to assess healthcare workers' adherence to Standard Precautions. Three studies also assessed healthcare workers' knowledge, and one measured rates of colonisation with methicillin-resistant Staphylococcus aureus (MRSA) among residents and staff of long-term care facilities. Because of heterogeneity in interventions and outcome measures, we did not conduct a meta-analysis. Education may slightly improve both healthcare workers' adherence to Standard Precautions (three studies; four centres) and their level of knowledge (two studies; three centres; low certainty of evidence for both outcomes). Education with visualisation of respiratory particle dispersion probably improves healthcare workers' use of facial protection but probably leads to little or no difference in knowledge (one study; 20 nurses; moderate certainty of evidence for both outcomes). Education with additional infection control support may slightly improve healthcare workers' adherence to Standard Precautions (two studies; 44 long-term care facilities; low certainty of evidence) but probably leads to little or no difference in rates of health care-associated colonisation with MRSA (one study; 32 long-term care facilities; moderate certainty of evidence). Peer evaluation probably improves healthcare workers' adherence to Standard Precautions (one study; one hospital; moderate certainty of evidence). Checklists and coloured cues probably improve healthcare workers' adherence to Standard Precautions (one study; one hospital; moderate certainty of evidence). Authors' conclusions: Considerable variation in interventions and in outcome measures used, along with high risk of bias and variability in the certainty of evidence, makes it difficult to draw conclusions about effectiveness of the interventions. This review underlines the need to conduct more robust studies evaluating similar types of interventions and using similar outcome measures.